Waste Paper Hydrolysis Analysis with Sulfuric Acid Catalyst using Response Surface Methodology - Panjaitan, Jabosar Ronggur Hamonangan; Octaviani, Conny; Sinabutar, Renata Margaretta (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2025)
Paper waste can cause environmental damage, so paper waste processing must be carried out. Paper waste which is a lignocellulosic compound can be processed with acid hydrolysis process to produce cellulose degradation products. In this research, waste paper hydrolysis was carried out using sulfuric acid with response surface methodology (RSM) optimization which the variables studied were mixing speed, time and S/L ratio. Based on the results of ANOVA test, it was known that mixing speed, time and solid liquid (S/L) ratio did not have a significant influence on %conversion. From the comparison of the independent variables, the mixing speed and time showed significantly influence %conversion compared to the S/L ratio. Higher %conversion was obtained from lower value of mixing speed, time and S/L ratio. In this study, 65% conversion was produced under operating conditions of 175 rpm stirring speed, 30 minutes reaction time, and 1:15 S/L ratio.